Antecedent aeolian dune topographic control on carbonate and evaporite facies: Middle Jurassic Todilto Member, Wanakah Formation, Ghost Ranch, New Mexico, USA. Issue 3 (22nd September 2018) - Kocurek, Gary; Martindale, Rowan C.; Day, Mackenzie; Goudge, Timothy A.; Kerans, Charles; Hassenruck‐Gudipati, Hima J.; Mason, Jasmine; Cardenas, Benjamin T.; Petersen, Eric I.; Mohrig, David; Aylward, Daniel S.; Hughes, Cory M.; et al.
Abstract: The Middle Jurassic Todilto Member of the Wanakah Formation is a carbonate and gypsum unit inset into the underlying aeolian Entrada Sandstone in the San Juan Basin. Field and thin section study of the uppermost Entrada and Todilto at Ghost Ranch, New Mexico, identified Todilto facies and their relationship to remnant Entrada dune topography. Results support the previous interpretation that the Entrada dunes, housed in a basin below sea level, were rapidly flooded by marine waters. Mass wasting of the dunes gave rise to sediment‐gravity flows that largely buried remnant dune topography, leaving ca 12 m of relief that defined the antecedent condition for Todilto deposition. Previously interpreted as seasonal varves deposited in a stratified water body, the Todilto is reinterpreted as a microbial biolaminite. Most diagnostic are organic‐rich laminae with structures characteristic of filamentous microbes and containing trapped aeolian silt, and clotted‐texture laminae with a fabric associated with calcification of extracellular polymeric substances. The spatial arrangement of Todilto facies is controlled by the dune palaeotopography. A continuous basal laminated mudstone thickens over the dune crest, reflecting the optimum conditions for microbial mat development, and is interpreted to have been deposited when marine waters submerged the topography. Subsequent drying caused emergence of the crestal area, and formation of tepee structures and a dissolution breccia. Gypsiferous mudflats and periodic ponds occupied the dune flanks and interdune area, with gypsum concentrated within the interdune area. Entrada sands remained unstable during Todilto deposition with common injection structures into the Todilto, and a remnant slope caused the downslope movement and folding of Todilto strata on the upper lee face. Although some expansion of the gypsum occurred in the subsurface, facies architecture fostered development of a dissolution front adjacent to the interdune gypsum body with section collapse of gypsiferous limestone on the dune flanks.